Failure of abdominal wall closure after intestinal transplantation: Identifying high‐risk recipients. Issue 11 (23rd October 2019) - Cloonan, Madeline R.; Fortina, Chaeli A.; Mercer, David F.; Vargas, Luciano M.; Grant, Wendy J.; Langnas, Alan N.; Merani, Shaheed
Abstract: Open abdomen and fascial dehiscence after intestinal transplantation increase morbidity. This study aims to identify recipient and donor factors associated with failure to achieve sustained primary closure (failed‐SPC) of the abdomen after intestinal transplant. We conducted a single‐center retrospective study of 96 intestinal transplants between 2013 and 2018. Thirty‐eight (40%) were adult patients, and 58 were pediatric patients. Median age at transplantation was 36.0 and 5.8 years, respectively. Failed‐SPC occurred in 31 (32%) patients. Identified risk factors of failed‐SPC included preexisting enterocutaneous fistula (OR: 6.8, CI: 2.4‐19.6, P  = .0003), isolated intestinal graft (OR: 3.4, CI: 1.24‐9.47, P  = .02), male sex in adults (OR: 3.93, CI: 1.43‐10.8, P  = .009), and age over four years (OR: 6.22, CI: 1.7‐22.7, P  = .004). There was no association with primary diagnosis and prior transplant with failed‐SPC. Donor‐to‐recipient size ratios did not predict failed‐SPC. There was an association between failed‐SPC and extended median hospital stay (100 vs 57 days, P  = .007) and increased time to enteral autonomy in pediatric patients. There is a relationship between failed‐SPC and a higher rate of laparotomy (OR: 21.4, CI: 2.78‐178.2, P  = .0003) and fistula formation posttransplant (OR: 11.4, CI: 2.83‐45.84, P  = .0005) in pediatric patients. Given inferior outcomes with failed‐SPC, high‐risk recipients require careful evaluation.